The potential of Cilembu sweet potato (Ipomoea batatas L.) as a growth medium for Staphylococcus aureus and Escherichia coli - Nuswantoro, Ari; Rahayu, Merda Sri; Fatayati, Imma; Syopingi, Syopingi; Maretalinia, Maretalinia (JURNAL INFO KESEHATAN, 2024)
The media aims to store, reproduce, and identify bacteria but has disadvantages such as being expensive, containing chemicals, and being easily damaged due to contamination. Therefore we need an alternative media that can overcome these limitations. Cilembu sweet potato (Ipomoea batatas, L.) is a natural ingredient that is easy to obtain and contains sufficient nutrients so it has the potential to be used as a basic ingredient for growth media. The purpose of this study was to determine the potential of Cilembu sweet potato flour as an alternative medium for the growth of Staphylococcus aureus and Escherichia coli bacteria with a quasi-experimental design. Cilembu sweet potato flour is obtained by cleaning, chopping, drying in the oven, crushing with a blender, and sifting the tubers to obtain fairly fine flour. The flour was dissolved in agar and then inoculated with S. aureus and E. coli, each with 16 replications. The results showed that the average number of S. aureus colonies was 119.12 CFU (169.2 CFU in control) while E. coli was 160.56 CFU (221.2 CFU in control). The Mann-Whitney test showed that there was a difference in the number of S. aureus colonies on alternative media and NA (p = 0.006 ≤ 0.05), but there was no difference between the number of E. coli colonies on alternative media and NA (p = 0.057 > 0.05). Finally, there was a difference in the number of S. aureus and E. coli colonies on alternative media (p = 0.04 ≤ 0.05). The nutritional composition shows that Cilembu sweet potato flour has more potential to replace NA as a growth medium for E. coli than for S. aureus.